2013
DOI: 10.7554/elife.01339
|View full text |Cite
|
Sign up to set email alerts
|

tRNA genes rapidly change in evolution to meet novel translational demands

Abstract: Changes in expression patterns may occur when organisms are presented with new environmental challenges, for example following migration or genetic changes. To elucidate the mechanisms by which the translational machinery adapts to such changes, we perturbed the tRNA pool of Saccharomyces cerevisiae by tRNA gene deletion. We then evolved the deletion strain and observed that the genetic adaptation was recurrently based on a strategic mutation that changed the anticodon of other tRNA genes to match that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
106
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 77 publications
6
106
2
Order By: Relevance
“…Further, the expression of the anticodon isoacceptor families, relative to each other, was stable across mammalian development. In yeast, tRNA genes can compensate for changing levels of expression of another member of their isoacceptor family, an effect demonstrated by systematic deletion of tRNA genes (Yona et al 2013;Bloom-Ackermann et al 2014). Our data are a first direct indication that a compensatory mechanism must also operate dynamically in mammals to stabilize the collective expression of a given isoacceptor family.…”
Section: Discussionmentioning
confidence: 68%
“…Further, the expression of the anticodon isoacceptor families, relative to each other, was stable across mammalian development. In yeast, tRNA genes can compensate for changing levels of expression of another member of their isoacceptor family, an effect demonstrated by systematic deletion of tRNA genes (Yona et al 2013;Bloom-Ackermann et al 2014). Our data are a first direct indication that a compensatory mechanism must also operate dynamically in mammals to stabilize the collective expression of a given isoacceptor family.…”
Section: Discussionmentioning
confidence: 68%
“…Such constraint is more likely to be too stringent for protein-coding genes overlaps. In contrast, tRNA gene sequences evolve rapidly and recent evidence showed that a simple secondary structure coupled with a specific anticodon may be sufficient to generate a functional tRNA, 47,48 or that incomplete cloverleaf structure may be repaired post-transcriptionally (e.g., tRNA His in this study).…”
Section: Discussionmentioning
confidence: 87%
“…Evolutionary importance of changes in the tRNA gene and energy efficiency with bacterial growth has already been well characterized. 20,54,55 The occurrence of Met in proteins is very infrequent (Fig. 6a), its internal occurrence would mean a higher metabolic cost.…”
Section: Discussionmentioning
confidence: 99%